An objective re‐evaluation of adaptive sample size re‐estimation: commentary on 'Twenty‐five years of confirmatory adaptive designs'. (10th February 2016) - Mehta, Cyrus; Liu, Lingyun
Abstract : Over the past 25 years, adaptive designs have gradually gained acceptance and are being used with increasing frequency in confirmatory clinical trials. Recent surveys of submissions to the regulatory agencies reveal that the most popular type of adaptation is unblinded sample size re‐estimation. Concerns have nevertheless been raised that this type of adaptation is inefficient.We intend to show in our discussion that such concerns are greatly exaggerated in any practical setting and that the advantages of adaptive sample size re‐estimation usually outweigh any minor loss of efficiency. Copyright © 2015 John Wiley & Sons, Ltd.